2022
DOI: 10.4049/jimmunol.208.supp.169.08
|View full text |Cite
|
Sign up to set email alerts
|

BCL6-dependent TCF-1+ progenitor cells maintain effector and helper CD4 T cell responses to persistent antigen

Abstract: Shortly after priming, the fate of activated CD4 T cells is segregated into BCL6+ follicular helper T (Tfh) and BCL6− effector (Teff) cells. However, it remains unknown how these subsets are sustained in the presence of chronic antigen stimulation. Using a combination of single cell- and population-based approaches, we show that in chronic viral infection, activated CD4 T cells differentiate into BCL6-dependent TCF-1+ progenitor cells with superior capacity to expand and give rise to both Teff and Tfh. They sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Notably, the relapse-effects predicted by our model for a chronic inflammation scenario are commonly found in several autoimmune disorders (9). While several factors have been identified that contribute to the emergence and stabilization of a chronic infection, our model simulations show that two data-derived constraints, namely negative feedback via IL-10 together with antigen-driven proliferation of precursor cells (34,46,47), are sufficient to capture the experimentally observed chronic Th cell response. Further, our model simulations show that the discovery of intermediate proliferative precursor cells that persist during chronic viral infection (34,46) is well in line with previously described infection kinetics (51).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Notably, the relapse-effects predicted by our model for a chronic inflammation scenario are commonly found in several autoimmune disorders (9). While several factors have been identified that contribute to the emergence and stabilization of a chronic infection, our model simulations show that two data-derived constraints, namely negative feedback via IL-10 together with antigen-driven proliferation of precursor cells (34,46,47), are sufficient to capture the experimentally observed chronic Th cell response. Further, our model simulations show that the discovery of intermediate proliferative precursor cells that persist during chronic viral infection (34,46) is well in line with previously described infection kinetics (51).…”
Section: Discussionmentioning
confidence: 68%
“…While several factors have been identified that contribute to the emergence and stabilization of a chronic infection, our model simulations show that two data-derived constraints, namely negative feedback via IL-10 together with antigen-driven proliferation of precursor cells (34,46,47), are sufficient to capture the experimentally observed chronic Th cell response. Further, our model simulations show that the discovery of intermediate proliferative precursor cells that persist during chronic viral infection (34,46) is well in line with previously described infection kinetics (51). Similar progenitor-like phenotypes have been found for exhausted CD8+ T cells (34), thus indicating a general motif of immunological decision-making.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation